Word Formation And Morphological Integration In Jazani Arabic - Ruthan, Mohammed Qasem (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Various studies have analyzed word formation in Standard Arabic. However, few have described it in colloquial Arabic, and none have discussed it in Jazani Arabic. To address that gap, this descriptive qualitative study analyzed words in Jazani Arabic in light of word formation and morphology. Data were collected via observations of everyday speech. In addition to morphological integrations, the study discusses five word-formation processes: 1) borrowing, 2) clipping, 3) hypocorism, 4) backformation, and 5) derivation. Based on this data, the study presents a novel morphological analysis for Jazani Arabic words. Borrowing was the most common process. Clipping was generally rare with common nouns but was familiar with proper names. While derivation was a fundamental process, it was complementary to backformation. Morphological integrations occurred across all of these word-formation processes. Nouns borrowed into Jazani Arabic were integrated into the morphology with an Arabic definite article, and borrowed verbs were integrated with a Jazani Arabic future marker. Clipping was predominantly attested with nouns, with no instances of it attested with verbs. Hypocorism showed similar but not identical patterns to those in other varieties of Arabic, while backformation was peculiar to Jazani Arabic. The study indicates that Jazani Arabic has distinctive morphological features and patterns.